Knowledge And Awareness On Various Types Of Fixed Appliances And Aligners Among Medical Students (Journal of Pharmaceutical Negative Results, 2022)
Background : Orthodontic fixed braces are a type of fixed orthodontic appliance that is used to rectify tooth alignment. Self-ligating braces, ceramic braces, Conventional braces,Aligners and lingual braces are among the different types of orthodontic braces commonly available for fixed orthodontic treatment . Despite the fact that there are many different types of fixed appliances , knowledge about these fixed appliances among the medical students is still questionable.The aim of the study was to assess the awareness of various types of orthodontic fixed appliances and aligners among the medical students.Materials And Methods : A set of 14 questionnaires was formulated and distributed among the study participants. The participants were asked to fill the questionnaire . The survey was done in an online forum. A total of 100 validated entries were collected. Data was entered into Microsoft Excel 2007 and analysed in SPSS V20. Associations between categorical variables were determined using Chi-square test. P < 0.05 was considered statistically significant.Results : The results shows that 78 % of the participants were aware of orthodontic speciality in dentistry and 86 % of the participants were aware of fixed and removable orthodontic treatment appliances.72 % Of the participants were having knowledge on various types of materials used in fixed orthodontic appliance. 53 % of them know about conventional and smart(Self ligating) technique in orthodontics and 72 % know about clear retainers. 64 % were aware that duration of orthodontic corrections may take upto 18 months. 72 % were aware that additional oral hygiene measures should be taken during the course of orthodontic treatment and retainers should be used after the completion of orthodontic corrections to prevent relapse.Conclusion : Healthcare providers are primary caregivers for a variety of health-related complaints. The present day medical students are future health care providers. In this study , the results show that medical students have good knowledge on dental malocclusion and various specialties in dentistry as well as orthodontics and fixed appliances and aligners. Furthermore, exposure to the dental sub- specialities , especially orthodontics would enable them to identify and educate on malocclusions and make informed referrals appropriately.